Une doxographie sunnite du IVe/Xe siècle ›Kitāb al-maqālāt‹ d'Abū al-ʿAbbās al-Qalānisī - Bou Akl, Ziad (Scientia Graeco-Arabica, 2021)
This book contains an edition and annotated translation of the only remaining doxographical fragments written by al-Qalānisī, a Sunni theologian contemporary of al-Aš'arī. The study preceding the edition gives an overview of 9th-century Sunni kalām. It sheds a new light on al-Qalānisī's positions and explains the reasons behind the success of al-Ašʿarī whose school relegated this early period of Sunni kalām.